A Systematic Review On Complications of Intrahepatic Cholestasis of Pregnancy - Sadia Chaudhary, Hafiz Hafeez Anjum, Muhammad Usman Khan, Amna Khurram, Uzma Nazim, Merub Maqsood Dar (Pakistan Journal of Medical & Health Sciences, 2022)
A potentially dangerous liver condition called intrahepatic cholestasis of pregnancy (ICP) can appear during pregnancy. Primarily manifesting in the third trimester, characteristic symptoms include pruritus (itching) of the soles and palms, elevated blood bile acid levels, and impaired liver function. Several medications have been demonstrated to significantly improve biochemical indicators and gestational age of birth in patients with ICP, and they also alleviate the pruritus experienced by the mother. The use of these drugs during pregnancy may have serious consequences. This systematic review aims to describe maternal and foetal outcomes related to ICP and identify major biochemical and clinical predictors of foetal problems in women diagnosed with ICP. To provide context for the current investigation, Google Scholar and PubMed were searched for articles published between 2012 and 2022. References and bibliographies were employed in manual searches in addition to internet resources. Critical Appraisal Skills Program (CASP) evaluated all selected research papers. Findings were presented using descriptive summary table besides critical analysis. Risks of adverse perinatal outcomes, such as stillbirth and early delivery, were associated with twin pregnancies with ICP. But, premature delivery and neonatal hypoxia are more common in IVF-created twin pregnancies than in naturally conceived twin births. Severe ICP effects are linked with higher risks of stillbirth, admission to a neonatal intensive care unit, and preterm delivery. Some perinatal issues are associated with a mother’s serum bile acid levels rising during pregnancy. Congenital disabilities, premature birth, and postpartum bleeding are all associated with ICP. Extreme instances of ICP frequently result in the abrupt and unexpected death of the fetus inside the uterus. ICP and stillbirth develop early in twin pregnancies. Therefore, delivering at 37 weeks may not be desirable. Enhancing fetal prognosis, particularly in twin pregnancies generated through IVF, requires early and correct diagnosis and proper medical intervention. To reduce the likelihood of an indicated preterm delivery, the decision to terminate a pregnancy in pregnancies created through IVF should be made carefully. Despite the fact that there was a clear link between ICP and preeclampsia and GDM, ICP did not raise the risk of stillbirth. Bile acid levels between the mother and fetus correlate, suggesting a causative link between BA levels, prenatal problems, and bad outcomes. Keywords: Intrahepatic cholestasis of pregnancy; pregnancy outcomes; gynecology; women health